A wise heart – about the state, law and politics in a dialogue between reason and religion - Borsiak, Maciej (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
The paper presents and comments on the discussions that took place between cardinal Joseph Ratzinger and philosopher Jürgen Habermas. It concerned the current secularization and a place of religion in a liberal constitutional state. This is an example of how this type of discourse can be carried out in a manner intended to reach an agreement and pointing to the benefits the two „spheres” can draw upon each other. The author attempts to identify a source of a similar diagnosis which is established by both thinkers as well as to indicate how conclusions of the discussions affect the perception of the role of law in the modern state.